2014
DOI: 10.1590/0103-9016-2013-233
|View full text |Cite
|
Sign up to set email alerts
|

Large scale artificial rearing of Anastrepha sp.1 aff. fraterculus (Diptera: Tephritidae) in Brazil

Abstract: Some species of the genus Anastrepha (Diptera: Tephritidae) are successfully managed by matching the sterile insect technique with parasitoid releases. Such strategies used in integrated pest management can be implemented only where insect mass-rearing programs are feasible. In this study, we show the process of domestication, rearing technology and quality control data obtained from 54 generations of Anastrepha sp.1 aff. fraterculus (Wiedemann, 1830) kept under fully artificial conditions. Eggs were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 15 publications
0
43
1
2
Order By: Relevance
“…1 aff. fraterculus by Walder et al (2014), our study showed that the PIR population is behaviourally, genetically, and morphologically different from the populations previously classified as either morphotype Brazilian-1 (Hern andez-Ortiz et al, 2004 or Anastrepha sp. 1 aff.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…1 aff. fraterculus by Walder et al (2014), our study showed that the PIR population is behaviourally, genetically, and morphologically different from the populations previously classified as either morphotype Brazilian-1 (Hern andez-Ortiz et al, 2004 or Anastrepha sp. 1 aff.…”
Section: Discussioncontrasting
confidence: 70%
“…Interestingly, studies evaluating A. fraterculus populations from Piracicaba have found flies in at least three hosts: Eugenia pyriformis , a.k.a. uvaia (Walder et al ., ); Malpighia emarginata , a.k.a. Barbados cherry (B. J. Paranhos, personal communication), and P. guajava , a.k.a.…”
Section: Discussionmentioning
confidence: 99%
“…An A. fraterculus population from Cena (Centro de Energia Nuclear na Agricultura, Piracicaba -Brazil), was reared following Walder et al (2014) to obtain late third-instar larvae. They were used in an experiment completely random designed, with five repetitions composed by a nine-centimeter Petri dishes (Rohde et al, 2012) with 12 larvae, in a dark climatic chamber (24±2 °C, U.R.…”
Section: Virulence To a Fraterculusmentioning
confidence: 99%
“…The trays were covered with a dark fabric, to simulate the conditions inside the fruit, and placed in shelves at room temperature (28 to 30°C) and relative humidity (85 to 95%). The diet and methodology used was based on Walder et al (2014). Collections of larvae were performed when they were about to pupate, in the third larval stage, separating them from the diets by washing in water and filtering in a plastic sieve; 30% of these larvae was used to maintain the breeding of fruit flies and 70% were subjected to parasitism.…”
Section: Rearing Of the Parasitoid Diachasmimorpha Longicaudata In Lamentioning
confidence: 99%